Legal Aspects of Environmental Governance Related to Renewable Energy Development - Nahruddin, Zulfan; Ahmad, Badu; Ibrahim, Muh. Akmal; Tang, Muhammad (Journal of Public Representative and Society Provision, 2024)
Renewable energy development is a cornerstone of global efforts to combat climate change and achieve sustainable development. This study, a comprehensive literature review, explores the legal and regulatory frameworks that govern renewable energy transitions at both international and national levels. The findings highlight the critical role of international agreements, such as the Paris Agreement and the United Nations Sustainable Development Goals, in setting the global agenda for renewable energy adoption. Additionally, national legal systems, including policies like feed-in tariffs, tax incentives, and priority grid access, are instrumental in translating international commitments into actionable strategies. Despite significant progress, the study identifies persistent challenges in legal and regulatory implementation, including policy inconsistency, insufficient harmonization of environmental and energy regulations, limited institutional capacity, and infrastructure deficiencies. These barriers are exacerbated in developing countries, where weak governance structures and socio-political resistance further hinder renewable energy deployment. The study underscores the need for stronger integration of environmental and renewable energy policies, capacity-building initiatives, and inclusive stakeholder engagement to overcome these challenges. By analyzing existing legal frameworks and their implementation challenges, this research contributes to the understanding of how governance systems can be optimized to accelerate renewable energy transitions. The findings provide valuable insights for policymakers, legal practitioners, and stakeholders aiming to enhance the effectiveness of renewable energy governance and achieve sustainable energy goals.